Development of a Sensor-Based Smart Coupling for Optimizing Fisherboat Propulsion Systems - Munandar, I K; Sadewo, R; Pratama, M (Jurnal MESIL (Mesin Elektro Sipil), 2025)
Small-scale fishing vessels frequently suffer propulsion system degradation due to torque imbalance and shaft vibration, leading to premature component failure and reduced fuel efficiency. This study designs a sensor-based smart coupling for real-time torque and vibration monitoring to enhance system reliability. The development process integrates 3D design (SolidWorks), structural validation via Finite Element Analysis (FEA), prototype fabrication using AISI 1045 steel, and strain gauge-accelerometer (MPU6050) sensors with ESP32 microcontroller. Performance testing under 500 Nm dynamic loads employed Von Mises stress interpretation and vibration amplitude thresholds. Results demonstrate the coupling withstands 500 Nm torque with 0.18 mm deformation (within material elastic limits), while the system detects misalignment anomalies within 3 seconds at 2.5 mm/s² vibration amplitude. Implementation on sub-20 GT vessels confirms this smart coupling improves operational reliability, reduces downtime, and offers a cost-effective solution.